The Influence of Multicultural Education on Tolerant Attitudes of Elementary School Students Literature Study - -, Almira chandra lalita; Zakiah, Linda; Rafli Haikal, Deffa; Aswati, Dewi (Jurnal Ijtihad, 2024)
ABSTRACT Multicultural education in elementary schools is a concept that presents multicultural values in learning to develop national character and minimize conflict in various regions. The purpose of writing this scientific article is to find out how multicultural education influences the tolerance attitude of elementary school students. This research was carried out using research. qualitative, literature study or literature research. The data taken comes from research that already exists on the internet. The results of the research show that multicultural education has a positive impact on the tolerance attitude of elementary school students. The conclusion is that multicultural education has an influence on the tolerance attitude of elementary school students. Keywords: Multicultural education, Tolerance, Literature Study